Brazil - Innovative Approaches to Extending Family Health Services - La Forgia, Gerard (World Bank, Washington, DC, 2012)
The recently completed Family Health Extension Project (FHEP) has provided support to Brazil's Family Health Program (Programa de Saude da Familia, or PSF) and allowed dramatic improvements in the coverage of basic health services. The project aimed to improve utilization and quality of publicly-financed health services by: (a) expanding coverage of the PSF in about 100 large municipalities, establishing well-articulated referral and counter-referral systems, and introducing performance-based financing and management arrangements; (b) establishing family health as a core element of health professional and para-professional training; and (c) strengthening the Ministry of Health's (MOH or Ministerio da Saude) capacity to monitor and evaluate PSF health services, policies, and training activities on a systematic basis.